Manganese biofortification in grapevine by foliar spraying improves volatile profiles of Cabernet Sauvignon grapes and wine sensory traits - Ruihua Ren; Miaomiao Wang; Lijian Zhang; Fuxian Ren; Bowei Yang; Huangzhao Chen; Zhenwen Zhang; Qingqing Zeng (Food Chemistry: X)
Manganese (Mn) is involved in plant metabolism as an enzyme cofactor. However, the role of Mn in the formation of volatile compounds in grapes has rarely been studied. To address this gap, this study explored the effect of foliar Mn application on the aroma traits of grapes and wine. Mn nutrient solutions at different concentrations (0 (CK), 300, 1200, and 2400 mg/L) were sprayed on grapevines in 2017 and 2018 and the volatile compounds, odor activity, and sensory features of grapes and wine were investigated. The results showed that Mn application significantly increased Mn content in grape leaves and fruits at harvest. Compared with CK, the total volatile content of grapes was significantly increased by Mn treatment in both years because of the promotion of the accumulation of alcohols and esters. Particularly, 1200 mg/L Mn treatment resulted in a higher sensory score than CK, especially in terms of intensity, duration, and harmony. Multivariate analysis and odor activity values jointly identified eight volatile compounds (ethyl acetate, phenylethyl acetate, and phenylethyl alcohol, etc.) as key odorants that contribute to the floral and fruity flavors of Mn-treated wine. Overall, this study indicated that a moderate concentration of Mn is beneficial for improving the fragrance characteristics of grapes and wines. The results have implications for micronutrient management of grapevines to improve wine flavor quality.